Rido among Maranaos in Pualas Lanao Del Sur - Macalisang, Daryl G. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2009)
This study investigates the occurrence of family feuds or rido among Maranaos in Pualas, Lanao del Sur and how these are managed. The study attempts to describe rido, the type of management resorted to the current status of the feud. There were 10 Maranao key informants and each one had experienced being part of the conflicting party. Each key informant also represents one case of rido.